Natural regeneration of herbaceous vegetation post – grassland fire in the Quengo Río Alto hamlet, Bambamarca, Hualgayoc, Cajamarca 2021 (LACCEI, 2024)
The increase in fires in recent years has had multiple consequences on ecosystems, reducing vegetation and initiating erosion processes and changes in natural processes. The causes of fires are considerable in the Cajamarca Region, being human activities directly or indirectly related to these events. The objective of this research is to evaluate the percentage of post-fire plant regeneration in pastures in the locality of Quengo Río Alto, Bambamarca, Cajamarca. To carry out this study, five representative areas were randomly selected with a size of 1 square meter, in order to estimate the values of their parameters (abundance and dominance) after a fire, the purpose of which was to enable cultivation areas, eliminate residual vegetation cover and control any type of weeds. During six months, quantitative information of individuals found was monitored, which resulted in a rapid process of herbaceous plant regeneration equivalent to 77.4% of the total herbaceous plant species found at the beginning, with Lachemilla Orbiculata as the dominant species, representing 40.5% of the herbaceous plant species.